The Impacts of China's Rise on the Pacific and the World - Huang, Wei-Chaio (W.E. Upjohn Institute, 2018)
This book provides the perspectives of a group of noted China experts on how China's economic expansion and internal reforms are impacting its neighbors in the Pacific region as well as the United States and the rest of the world.